2013
DOI: 10.1016/j.jsis.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Mobility at work

Abstract: a b s t r a c tInnovations in mobile technology shape how mobile workers share knowledge and collaborate on the go. We introduce mobile communities of practice (MCOPs) as a lens for understanding how these workers self-organize, and present three MCOP case studies. Working from contextual ambidexterity, we develop a typology of bureaucratic, anarchic, idiosyncratic and adhocratic MCOPs. We discuss how variations in the degree of organizational alignment and individual discretion shape the extent to which these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Thus, contextual ambidexterity relies on decision making and organizational structures that provide a suitable environment for managing tradeoffs in which an individual manages the conflicting goals, rather than engraining ambidexterity into organizational characteristics [27], [34]. A prior study suggests a typology of different work practices with alternative implications for performance and innovativeness [45]. Other theoretical advances on contextual ambidexterity seek to understand the nomological net of contextual ambidexterity in greater depth.…”
Section: Contextual Ambidexteritymentioning
confidence: 99%
“…Thus, contextual ambidexterity relies on decision making and organizational structures that provide a suitable environment for managing tradeoffs in which an individual manages the conflicting goals, rather than engraining ambidexterity into organizational characteristics [27], [34]. A prior study suggests a typology of different work practices with alternative implications for performance and innovativeness [45]. Other theoretical advances on contextual ambidexterity seek to understand the nomological net of contextual ambidexterity in greater depth.…”
Section: Contextual Ambidexteritymentioning
confidence: 99%
“…These workers perform knowledge-intensive work, enjoy a relative degree of autonomy, and have flexible working arrangements (Cavazotte, Lemos, & Villadsen, 2014). Moreover, they are dependent on information to execute their activities (Kietzmann et al, 2013). Their tasks are rarely repetitive and require a variety of abilities and resources to be accomplished (Cavazotte et al, 2014;Harmer & Pauleen, 2012;Kietzmann et al, 2013).…”
Section: The Context Of Mobile Work and Its Challengesmentioning
confidence: 99%
“…Previous literature already indicated that one of the main challenges is the MKW's relationship with their colleagues, affecting not only the related learning and collaborative processes, but also their participation in organizational activities in general (Koroma, Hyrkkänen, & Vartiainen, 2014). Working alone restricts the MKW's opportunities to form and keep up interpersonal relationships (Kietzmann et al, 2013), increases their lack of support, and also generates the feeling of being invisible, or not included, in the parent organization (Koroma et al, 2014). Working on the move can negatively affect organizational inclusion and the sense of belonging to a work team (Chen & Nath, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviewees are thus considered as agents of change and members of a community of practice. A community of practice, after Lave and Wenger [230], is a group of people who share a craft or a profession (food issues here) and they share experiences over time, common sense making and self-regarding, either physically or virtually [231,232]. Although the food professionals live in different countries and work in different domains of the food system, they are all connected via their Twitter account, where they regularly post messages on food-related issues.…”
Section: Describing the Sample: Food System Professionals With Socialmentioning
confidence: 99%